2020
DOI: 10.1002/ecy.3139
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐evolutionary dynamics of range expansion

Abstract: Understanding the movement of species' ranges is a classic ecological problem that takes on urgency in this era of global change. Historically treated as a purely ecological process, range expansion is now understood to involve eco-evolutionary feedbacks due to spatial genetic structure that emerges as populations spread. We synthesize empirical and theoretical work on the eco-evolutionary dynamics of range expansion, with emphasis on bridging directional, deterministic processes that favor evolved increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(168 citation statements)
references
References 102 publications
2
136
2
Order By: Relevance
“…In the 1940 s, Simpson posited that species could enter new ‘adaptive zones’ (Simpson, 1945; Simpson, 1953) via specific events, including dispersal into new habitats, extirpation of predators, or through ‘key innovations’, namely, those that relax or fundamentally change the prevailing environmental sources of natural selection (Miller, 1949; Rabosky, 2017). Since then, there has been an accumulation of evidence for rapid phenotypic evolution over short time scales (Carroll et al, 2007), with perhaps some of the best examples of this phenomenon coming from range‐expanding species (Miller et al, 2020). During colonisation, consumers often encounter new food resources and undergo shifts in their trophic niche, culminating in the evolution of associated behavioural, morphological and physiological traits (Des Roches et al, 2016; Herrel et al, 2008; Leaver & Reimchen, 2012; Renaud et al, 2018).…”
Section: Metabolic Adaptation and Consumer Diversificationmentioning
confidence: 99%
“…In the 1940 s, Simpson posited that species could enter new ‘adaptive zones’ (Simpson, 1945; Simpson, 1953) via specific events, including dispersal into new habitats, extirpation of predators, or through ‘key innovations’, namely, those that relax or fundamentally change the prevailing environmental sources of natural selection (Miller, 1949; Rabosky, 2017). Since then, there has been an accumulation of evidence for rapid phenotypic evolution over short time scales (Carroll et al, 2007), with perhaps some of the best examples of this phenomenon coming from range‐expanding species (Miller et al, 2020). During colonisation, consumers often encounter new food resources and undergo shifts in their trophic niche, culminating in the evolution of associated behavioural, morphological and physiological traits (Des Roches et al, 2016; Herrel et al, 2008; Leaver & Reimchen, 2012; Renaud et al, 2018).…”
Section: Metabolic Adaptation and Consumer Diversificationmentioning
confidence: 99%
“…Within-species trait variability has reverberating impacts across organisation levels, from populations to ecosystem functioning (Des Roches et al, 2018; Jacob et al, 2019; Little et al, 2019; Raffard et al, 2019; Violle et al, 2012). Thus, knowing how phenotypes are redistributed in space during range expansions and range shifts is likely key to understand the ecological and evolutionary dynamics at play in the resulting communities (Cote et al, 2017; Miller et al, 2020; Renault et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to again consider eco‐evolutionary feedbacks within the system. For example, evolution can alter the speed of species' range shifts and thus any attempts to estimate range shifts need to account for evolution (Miller et al, 2020; Nadeau & Urban, 2019). Our review revealed an array of methods for estimating connectivity, including telemetry, movement ecology modeling, and gene flow estimation.…”
Section: Comparison Of Adaptive Capacity and Adaptive Potential Researchmentioning
confidence: 99%